2014
DOI: 10.3109/00365548.2014.930967
|View full text |Cite
|
Sign up to set email alerts
|

Spleen enlargement is a common finding in acute Puumala hantavirus infection and it does not associate with thrombocytopenia

Abstract: The pathogenesis of thrombocytopenia in Puumala hantavirus (PUUV) infection is probably multifactorial. We aimed to evaluate the possible spleen enlargement during acute PUUV infection, and to determine its association with thrombocytopenia and disease severity. Magnetic resonance imaging (MRI) of the spleen was performed in 20 patients with acute PUUV infection. MRI was repeated 5-8 months later. The change in spleen length was compared with markers describing the severity of the disease. In all patients, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…[27,32] Neither seems enhanced clearance or pooling of platelets in the enlarged spleen to be involved, as indicated by a previously recorded lack of association of thrombocytopenia and spleen size in PUUV induced HFRS. [33] Endothelial activation markers associate with thrombocytopenia [34] and pathogenic hantaviruses are known to direct the adherence of quiescent platelets through b3-integrin to the surface of infected endothelial cells [35] and specifically to PUUV particles. [36] The adherence of platelets may result in altered platelet activation and decreased circulating platelet count as well as a loss of vascular integrity.…”
Section: Discussionmentioning
confidence: 99%
“…[27,32] Neither seems enhanced clearance or pooling of platelets in the enlarged spleen to be involved, as indicated by a previously recorded lack of association of thrombocytopenia and spleen size in PUUV induced HFRS. [33] Endothelial activation markers associate with thrombocytopenia [34] and pathogenic hantaviruses are known to direct the adherence of quiescent platelets through b3-integrin to the surface of infected endothelial cells [35] and specifically to PUUV particles. [36] The adherence of platelets may result in altered platelet activation and decreased circulating platelet count as well as a loss of vascular integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Koskela et al. (61) reported a spleen length increased (median = 129 mm) in the acute phase in 20 consecutive patients compared with a control phase (median = 111 mm), 196 days later on average. The median change was 15 mm in the spleen length (61).…”
Section: Abdominal Imaging Findingsmentioning
confidence: 99%
“…The spleen contains approximately one third of the body's platelets content illustrating its role in controlling the balance of available blood platelets and hence preventing thrombocytopenia (Bassenge, 1996 ). Data from a limited number of severe NE patients demonstrates venous congestion, splenomegaly, and variable amounts of antigen-positive ECs in the spleen, presumably sinusoidal lining cells (Hautala et al, 2002 ; Koskela et al, 2014 ; Sironen et al, 2017 ). However, to date, there is no association between enhanced sequestration of blood platelets in the spleen and the pathogenesis of thrombocytopenia during HFRS/NE (Koskela et al, 2014 ).…”
Section: Hfrs/ne In Humans and Disease Modelsmentioning
confidence: 99%
“…Data from a limited number of severe NE patients demonstrates venous congestion, splenomegaly, and variable amounts of antigen-positive ECs in the spleen, presumably sinusoidal lining cells (Hautala et al, 2002 ; Koskela et al, 2014 ; Sironen et al, 2017 ). However, to date, there is no association between enhanced sequestration of blood platelets in the spleen and the pathogenesis of thrombocytopenia during HFRS/NE (Koskela et al, 2014 ). The most likely explanation of the pathogenesis of thrombocytopenia during HFRS/NE, seems to be peripheral consumption (adherence to ECs), since several bone marrow studies showed a normal morphogenesis of platelets (Lee, 1987 ; Lutteke et al, 2010 ).…”
Section: Hfrs/ne In Humans and Disease Modelsmentioning
confidence: 99%